Effect of Blended Learning Strategy on Students’ Academic Achievement in English Language in Public Senior Secondary Schools in Ebonyi State - Igwe, M. U.; Agwu, S. N. (Journal of Research in Adult and Continuing Education, 2025)
This study examined effect of blended learning strategy on students’ academic achievement in English Language in public senior secondary schools in Ebonyi State. The study adopted quasi-experimental design, specifically non-equivalent control group design or pretest post-test control group design. The population of the study was 19,688 senior secondary two (SSII) students of Ebonyi state while the sample size was 85 senior secondary two (SSII) students of two intact classes drawn from two co-educational public secondary schools using purposive technique. Each of the two intact classes of the respective schools was assigned to experimental and control groups. The experimental group was taught using blended learning while the control group was taught with lecture method. Data were collected using English Language Achievement Test (ELAT). The Pretest was conducted for both the experiment (treatment) and control groups. The experimental group, received treatments using blended learning while the control group was taught using traditional lecture method. Findings showed that: students taught English Language using Blended learning had significantly higher mean achievement score than students taught using lecture method; there was no significant difference in the mean achievement scores of male and female students taught English Language using blended learning; and gender and instructional strategies had no significant interaction effect on the mean achievement scores of students taught English Language.